USP14 regulates DNA damage repair by targeting RNF168-dependent ubiquitination. Issue 11 (2nd November 2018) - Sharma, Arishya; Alswillah, Turkeya; Singh, Kamini; Chatterjee, Payel; Willard, Belinda; Venere, Monica; Summers, Matthew K.; Almasan, Alexandru
ABSTRACT: Recent reports have made important revelations, uncovering direct regulation of DNA damage response (DDR)-associated proteins and chromatin ubiquitination (Ubn) by macroautophagy/autophagy. Here, we report a previously unexplored connection between autophagy and DDR, via a deubiquitnase (DUB), USP14. Loss of autophagy in prostate cancer cells led to unrepaired DNA double-strand breaks (DSBs) as indicated by persistent ionizing radiation (IR)-induced foci (IRIF) formation for γH2AFX, and decreased protein levels and IRIF formation for RNF168, an E3-ubiquitin ligase essential for chromatin Ubn and recruitment of critical DDR effector proteins in response to DSBs, including TP53BP1. Consistently, RNF168-associated Ubn signaling and TP53BP1 IRIF formation were reduced in autophagy-deficient cells. An activity assay identified several DUBs, including USP14, which showed higher activity in autophagy-deficient cells. Importantly, inhibiting USP14 could overcome DDR defects in autophagy-deficient cells. USP14 IRIF formation and protein stability were increased in autophagy-deficient cells. Co-immunoprecipitation and colocalization of USP14 with MAP1LC3B and the UBA-domain of SQSTM1 identified USP14 as a substrate of autophagy and SQSTM1. Additionally, USP14 directly interacted with RNF168, which depended on the MIU1 domain of RNF168. These findings identify USP14 as a novel substrate of autophagy and regulation of RNF168-dependent Ubn and TP53BP1 recruitment by USP14 as a critical link between DDR and autophagy. Given the role of Ubn signaling in non-homologous end joining (NHEJ), the major pathway for repair of IR-induced DNA damage, these findings provide unique insights into the link between autophagy, DDR-associated Ubn signaling and NHEJ DNA repair. Abbreviations: ATG7: autophagy related 7; CQ: chloroquine; DDR: DNA damage response; DUB: deubiquitinase; HR: homologous recombination; IR: ionizing radiation; IRIF: ionizing radiation-induced foci; LAMP2: lysosomal associated membrane protein 2; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MIU1: motif interacting with ubiquitin; NHEJ: non homologous end-joining; PCa: prostate cancer; TP53BP1/53BP1: tumor protein p53 binding protein 1; RNF168: ring finger protein 168; SQSTM1/p62 sequestosome 1; γH2AFX/γH2AX: H2A histone family member X: phosphorylated, UBA: ubiquitin-associated; Ub: ubiquitin; Ubn: ubiquitination; USP14: ubiquitin specific peptidase 14.